Peran Unit Dikyasa Melalui Dikmas Lantas Dalam Mengurangi Pelanggaran Kendaraan Bermotor Roda Dua Di Kalangan Pelajar SMA Di Wilayah Polresta Cirebon - Danubrata, Muhammad Arief (Police Studies Review, 2020)
This research aims to describe the role of Unit of the traffic unit of the police of Cirebon Polresta through Diknas then in reducing the breach of motor vehicle two wheel among high school students in the territory of Cirebon Polresta. The theories and concepts used by the authors in answering problems are management theory, communication theory, concept of the role, the concept of traffic violations, and the concept of Dikmas thus. The research was done with a qualitative approach and used the type of field research. The findings of this research is the role of the Dikyasa unit through Dikmas then in reducing the breach of motorised vehicle of two wheels among high school students in Cirebon Polresta is a vital thing, but still a little to the high school students. In the implementation of Dikmas then, the implementation of POAC management theory is needed to be applied to the role of Dikmas then and communication theory to be accepted by high school students. The research findings indicate an internal, unbalanced factor between the area of Cirebon Regency, the number of high school students, and the number of Dikyasa Unit personnel. In addition, there are external factors also derived from the lack of awareness of the driving of high school students in the road traffic. This factor makes the implementation constraints Dikmas then become less maximum. Based on the results of the research, the author suggests that the management of personnel members of Satdan, especially the member of Dikyasa Unit is done better and can maximize efforts in reducing traffic violations among high school students in Cirebon's Polresta law area.